1996
DOI: 10.1111/j.1365-2044.1996.tb14992.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative parental anxiety

Abstract: SummaryThis stuclqj attempts to identijy the incidence and specific sources of anxiety in the parents of children udniitted to hospital focused on how parental attitudes may contribute to the child's response in this situation [I, 2,6], rather than on the detrimental effects upon the parents themselves and the potential for the development of stress-induced psychological illness states.The aim of this study was to assess the incidence of clinically significant anxiety and its specific sources in a group of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 20 publications
4
49
1
2
Order By: Relevance
“…Parents were very anxious at the time of the presurgical assessment clinic and this did not diminish or increase on the day of surgery and is consistent with previous research on parental preoperative anxiety (5,6). Anxiety was not related to the child's previous anesthetic or type of surgery, in contrast to previous research (6) and may indicate that unmet information needs or other factors contribute to high parental anxiety.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Parents were very anxious at the time of the presurgical assessment clinic and this did not diminish or increase on the day of surgery and is consistent with previous research on parental preoperative anxiety (5,6). Anxiety was not related to the child's previous anesthetic or type of surgery, in contrast to previous research (6) and may indicate that unmet information needs or other factors contribute to high parental anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the majority of the parents, 56% (23) stated they would have preferred to receive the information about anesthetic at the presurgical assessment clinic visit. However, 31% (6) of those who received the information by post and 14% (3) of those who received the information at the presurgical assessment clinic said that they preferred to receive the information by post.…”
Section: Resultsmentioning
confidence: 99%
“…( 12), Thompson et al . ( 13) and Vessey et al . ( 14), who all reported extreme parental discomfort by the presence at mask induction of anaesthesia, and recommended more effective parent–staff relationship and utilization of parents at that time.…”
Section: Discussionmentioning
confidence: 95%
“…Avoidance is a coping mechanism that decreases anxiety. Previous studies assessing noncompliance and procrastination of medical procedures demonstrated that when a situation is a perceived as threatening, it leads to a higher anxiety, and this in turn may lead to adopt a coping mechanism of avoidance, procrastination or noncompliance [23,48,53,54].…”
Section: Tablementioning
confidence: 99%